AB0414 Mycophenolate Mofetil and Deflazacort in Neuropsychiatric Lupus: A Retrospective Study. (15th July 2016) - Gupta, N.; Mandal, S.K.; Mathew, J.; Pulukool, S.; Goel, R.; Mathew, A.J.; Nair, A.; Sebastian, T.; Danda, D.
Abstract : Background: Mycophenolatemofetil (MMF) is an effective therapeutic agent with high safety profile in the management of lupus nephritis. Objectives: This retrospective study was conducted to assess the efficacy and side effect profile of MMF and deflazacort in patient with neuropsychiatry lupus (NP SLE). Methods: Patients of SLE by SLICC 2012 between January 2005 and May 2015 satisfying ACR 1997 criteria for NP SLEwere recruited from department of Clinical immunology & Rheumatology, Christian Medical College, Vellore, India. Patients consistently using MMF as the second line agent were enrolled. Clinical response, SLEDAI and side effect profile were noted from electronic medical records. Clinical improvement was defined as remission of presenting neurological symptom with no new neurological symptom. Results: Of the 140 patients with NP SLE, 88 fulfilled the inclusion criteria. Mean age of the cohort was 25.51±7.82 years with female to male ratio of 84: 4. Median duration of neurological symptoms prior to presentation was 90 (17.5 – 317.5) days. Median duration of follow up was 33 (3–129) months. Among the various NP SLE manifestations, seizure was the most common presentation (n=37, 42.05%). Renal involvement was seen in 49 (55.7%) patients. MRI findings varied from white and grey matter hyper -intensities to ventricular dilatation and brain atrophy. Of the 88 patients on MMF, 13 were pulsed with 1 gm methylprednisolone for 3 days and 8 were pulsed with oral dexamethasone pulse of 40 mg/day for 5 days. Subsequently, oral steroids was started at a dose of 1 mg/kg & tapered after 8–12 weeks to mean deflazacortdose (prednisoloneeqyuivalent) of 11.07±7.77 (9.33±5.88) mg at the end of 1 year. IMAGE: Showing various parameters at baseline and follow up as below. Major adverse events included lower respiratory tract infection in 2 patients and 1 fatality due to sepsis from gastroenteritis. Of 68 patient with median duration of follow up of 33 (3–129) months, 17 were only on MMF without any steroids, 14 not on either steroids or MMF and 6 were only on maintenance low dose steroids. Deflazacort was equally efficacious and had better toxicity profile than prednisolone. Conclusions: In patients of NP SLE, MMF is efficacious in inducing remission and preventing relapse of disease with a good safety profile. Deflazacort was found to have superior toxicity profile with equal efficacy as to prednisolone in NP SLE patients. Disclosure of Interest: None declared